THE INFLUENCE OF WORK STRESS AND MOTIVATION ON JOB PERFORMANCE (CASE STUDY AT KANTOR SEKRETARIAT MINAHASA SELATAN) - Lumi, Regina (Sam Ratulangi University, 2015)
ABSTRACT Work stress is a part that always associated with the employees’ productivity. Work stress is an imbalance between the personalities of the employee with work and can occur in all working conditions. Motivation can push the spirit of employee to work hard and providing all their capabilities of skill to achieve the company goals. The study aims to find out the influence of work stress and motivation on job performance in Kantor Secretariat Minahasa Selatan. Multiple regressions analysis which enables the researcher to analyze the influence of the independent variables to the dependent variable has used. This study may imply that the contribution of independent variable on dependent variable while the remaining is affected by other variables not examined in this study. The result shows that there is significant simultaneous and partial influence on Job Performance in Kantor Sekretariat Minahasa Selatan. Keywords: Work Stress, Motivation, Job Performance